Young Deceivers: Executive Functioning and Antisocial Lie‐telling in Preschool Aged Children. Issue 1 (11th January 2016) - Williams, Shanna; Leduc, Karissa; Crossman, Angela; Talwar, Victoria
Abstract : The present study examined the emergence of antisocial lie‐telling in very young children. Lie‐telling was studied in relation to executive functioning skills and children's abilities to identify both truths and lies. A total of 65 children ( Mage in months  = 31.75, SD  = 1.87) participated in a modified temptation resistance paradigm (TRP; designed to elicit spontaneous lies). Executive functioning was measured through an inhibitory control task and a forward search planning task. The Truth/Lie Identification task was administered (Lyon, Carrick, & Quas, 2010 ) to measure children's abilities to accurately distinguish truths and lies. During the TRP, a total of 89.23% children peeked at the toy when a research assistant left the room, and of those children, 29.31% lied to the research assistant. Significant differences on executive functioning measures were found between lie‐tellers and confessors, as well as for the Truth/Lie Identification task. Lie‐tellers had higher scores on measures of inhibitory control and forward search planning. Lie‐tellers also had higher accuracy on the Truth/Lie Identification task than confessors. This study provides a unique contribution to the literature by examining 2.5‐year‐old children's emerging lie‐telling abilities, a relatively understudied age during which fledgling lie‐telling emerges. Copyright © 2016 John Wiley & Sons, Ltd.